The genetic composition of the Traditional Irish Horse – towards the development of a DNA-ancestry test for the preservation of traditionally bred Irish Sport Horses - Beatrice McGivney; Deirdre Harty; Alison Corbally; Emmeline Hill (Genetic Resources, 2023)
The traditionally bred Irish Sport Horse, known as the Traditional Irish Horse, is an important cultural asset to horse genetic resources in Ireland. We tested the hypothesis that the Irish Sport Horse, which was originally developed from the Irish Hunter, may contain a genetic background distinct from European horse populations that would be valuable to preserve. Using genome-wide single nucleotide (SNP) data, the results show that Traditional Irish Horses (with confirmed pedigrees) have lower levels of European ancestry components than other Irish Sport Horses. These results indicate that measurement of the levels of European ancestry components in the Irish Sport Horse may assist in the preservation of traditional Irish lineages.